Studies on the potential of waste soda lime silica glass in glass ionomer cement production - Francis Thoo, Voon Wai; Zainuddin, Norhazlin; Matori, Khamirul Amin; Abdullah, Siti Anisah (Hindawi Publishing Corporation, 2013)
Glass ionomer cements (GIC) are produced through acid base reaction between calcium-fluoroaluminosilicate glass powder and polyacrylic acid (PAA). Soda lime silica glasses (SLS), mainly composed of silica (SiO2), have been utilized in this study as the source of SiO2 for synthesis of Ca-fluoroaluminosilicate glass. Therefore, the main objective of this study was to investigate the potential of SLS waste glass in producing GIC. Two glasses, GWX 1 (analytical grade SiO2) and GWX 2 (replacing SiO2 with waste SLS), were synthesized and then characterized using X-ray diffraction (XRD) and energy dispersive X-ray (EDX). Synthesized glasses were then used to produce GIC, in which the properties were characterized using Fourier transform infrared spectroscopy (FT-IR) and compressive test (from 1 to 28 days). XRD results showed that amorphous glass was produced by using SLS waste glass (GWX 2), which is similar to glass produced using analytical grade SiO2 (GWX 1). Results from FT-IR showed that the setting reaction of GWX 2 cements is slower compared to cement GWX 1. Compressive strengths for GWX 1 cements reached up to 76 MPa at 28 days, whereas GWX 2 cements showed a slightly higher value, which is 80 MPa.